Hepatitis B Virus and Hepatitis Delta Virus infection in Colombian indigenous communities (2022)
ABSTRACT: Despite the universal vaccine program, there are still high Hepatitis B prevalence regions such as the Amazon Basin. Indeed, the World Health Organization estimates 296 million people with chronic Hepatitis B Virus (HBV) infection and 820,000 deaths/year related to this infection over the world. Moreover, Hepatitis Delta Virus (HDV) affects 4.5% of individuals with chronic Hepatitis B. HDV is a satellite of HBV considering that the assembly of HVD virions depends upon the HBV surface antigen (HBsAg). HBV and HDV are particularly prevalent in indigenous communities from the Amazon Basin probably due to geographic, socioeconomic, and cultural factors that hinder access to the health system.